Analisis Pemikiran Al-Ghazali tentang Evolusi Pasar dan Relevansinya dalam Ekonomi Kontemporer - ayu lestari, Intan; Restu Putri, Ai Indri; Marlina, Lina; Diyana, Ana Fauziya (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The purpose of this study is to analyze Al-Ghazali's views on market development and assess their relevance in the current economic context. The method used in this study is a qualitative method with a literature research approach, through a study of Al-Ghazali's works and literary sources related to Islamic economics. The research findings indicate that Al-Ghazali argued that markets grow naturally due to the human need to fulfill each other's needs through the exchange of goods and services. He also emphasized the importance of ethical values in economic activities, such as honesty, justice, and the prohibition of fraud and hoarding practices. This view indicates that market mechanisms are not only influenced by economic elements, but also by moral and social principles. In this regard, Al-Ghazali's ideas are still relevant in the modern economy, particularly in encouraging fair, ethical economic practices that focus on the welfare of society. Thus, Al-Ghazali's thoughts can be used as a conceptual basis for developing a more ethical and sustainable contemporary economy.